A novel synthesis of new antibacterial nanostructures based on Zn-MOF compound: design, characterization and a high performance application. Issue 1 (January 2020) - Akbarzadeh, Fatemeh; Motaghi, Mehdi; Chauhan, Narendra Pal Singh; Sargazi, Ghasem
Abstract: In this study, the novel zinc metal-organic frameworks (MOF) nanostructure has been employed, which was developed using an affordable, environmental friendly, efficient and fast method of ultrasound-assisted reverse micelle (UARM). These nanostructures were identified with various techniques such as FT-IR, XRD, BET, SEM, TG-DSC, TEM and EDS. It was found that the Zn-MOF samples have favorable physicochemical properties. The impact of experimental parameters of the UARM method is effective on the resulting properties, such as high surface area of the products that increases the interactions between the Zn-MOF nanostructure and bacteria.Their antibacterial activities were investigated using diffusion methods in agar and also with dilutions of Zn-MOF samples. Antibiotics (tetracycline and ampicillin) and their anti-biofilm effects were evaluated using microplate method. Obtained results revealed that the Zn-MOF nanostructures have high antibacterial properties which, could be due to the nature of the applied Zn-MOF as well as the optimization process. The Zn- MOF nanostructures could be a novel antibacterial material as biocatalyst processes. Abstract : Biotechnology; Microbiology; Zn-MOF, UARM method, Growth inhibitory concentration, Biofilm